Effect of antimony dopant on the structural properties of CdSe crystalline chalcogenides. (2022) - Yadav, Kavita; Sangwan, Reetu; Barala, Monika; Mohan, Devendra; Sanghi, Sujata
Abstract: The present work focuses on the synthesis of CdSe, and Sb doped CdSe by the melt quench technique and investigates the physical properties of Sb doping on CdSe. The bulk samples were characterized by X-ray Diffractometer (XRD). The crystallite size and crystallinity have been determined. The crystalline nature of prepared samples was understood to be due to the nucleation growth during the melt quench of the sample. Crystallite size was determined by Scherrer's formula and Williamson Hall's (W-H) plot method. These methods were used for comparing the crystallite size and for the determination of microstructural strain. In the W-H plot, the Uniform deformation Model (UDM) was used. Crystallite size calculated by Scherrer's formula was found to be 45.26 nm, 42.84 nm, and by the W-H plot 72.57 nm, 47.14 nm, respectively.